2018
DOI: 10.1017/s0031182018000203
|View full text |Cite
|
Sign up to set email alerts
|

Phloroglucinol derivatives fromHypericumspecies trigger mitochondrial dysfunction inLeishmania amazonensis

Abstract: Bioactive molecules isolated from plants are promising sources for the development of new therapies against leishmaniasis. We investigated the leishmanicidal activity of cariphenone A (1), isouliginosin B (2) and uliginosin B (3) isolated from Hypericum species. Promastigotes and amastigotes of Leishmania amazonensis were incubated with compounds 1-3 at concentrations 1-100 µm for 48 h. The anti-promastigote effect of compounds was also tested in combinations. The cytotoxicity against macrophages and human ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Promastigotes stained with MitoTracker R Red CM-H2XROS and rhodamine 123 revealed that this compound increased the m , while MitoSOX staining revealed an increase in the mitochondrial superoxide production. It is important to highlight that the maintenance of m is vital for cell metabolic processes and consequently for cell survival (Fonseca-Silva et al, 2011); thus both increased (hyperpolarization) or decreased (depolarization) m can have negative consequences for mitochondrial integrity (Dagnino et al, 2018). In addition, superoxide generation has also been related to mitochondrial dysfunction, being indicative of damage to this organelle (Lafargue et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Promastigotes stained with MitoTracker R Red CM-H2XROS and rhodamine 123 revealed that this compound increased the m , while MitoSOX staining revealed an increase in the mitochondrial superoxide production. It is important to highlight that the maintenance of m is vital for cell metabolic processes and consequently for cell survival (Fonseca-Silva et al, 2011); thus both increased (hyperpolarization) or decreased (depolarization) m can have negative consequences for mitochondrial integrity (Dagnino et al, 2018). In addition, superoxide generation has also been related to mitochondrial dysfunction, being indicative of damage to this organelle (Lafargue et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the maintenance of an appropriate mitochondrial membrane potential (DYm) is essential for Leishmania survival (36,37). Here, we demonstrate that IS with leishmanicidal activity caused an increase in ROS production (Figures 4A, B (29), and depolarization can be preceded by a transient hyperpolarization as the last attempt by cells to avoid death (39). Moreover, all six IS presenting leishmanicidal activity caused plasma membrane alterations (Figures 4A, B), indicating cell death involving necrosis (40).…”
Section: Imidazolium Salts Reduce the Intracellular Survival Of L Ama...mentioning
confidence: 81%
“…Subsequently, the parasites were washed three times with 0.2 M phosphate buffer pH 7.4 and post-fixed in a solution of 2% OsO 4 with 0.2 M phosphate buffer (1:1) for 45 min at room temperature. All samples were dehydrated in a graded series of acetone in water from 30% to 100%, critical point dried using CO 2 , mounted on metal stubs, and coated with gold for observation in a field emission scanning electron microscope (Inspect F50, FEI) ( 29 ). In addition, the IS C 16 MImMes and C 16 MImCl, tested in our previous study ( 13 ), were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Leishmania has a single mitochondria, thus mitochondrial dysfunction and energy metabolic plasticity in Leishmania is more restricted when compared with thousands of mitochondria that can be detected in mammalian cells ( Menna-Barreto and de Castro, 2014 ; Dagnino et al., 2018 ). In this regard, when considering cytotoxicity against macrophages, monomethylsulochrin showed selectivity index of 18.0.…”
Section: Resultsmentioning
confidence: 99%